A arte de combinar: uma proposta metodológica para o Ensino Médio baseada na resolução de problemas - Peixoto, Priscilla Costa (2019)
In this paper we will present a methodological proposal for the teaching of Combinatorial Analysis, based on Problem Based Learning (ABProb), in search of a more efficient method for its learning. To this end, we will start with a brief historical background of high school and its standardization in Brazil, presenting some of the expectations of its new proposal and some active methodologies, focusing on its ideals. We will emphasize ABProb, motivated by the recommendations of the National Curriculum Parameters, the Common National Curriculum Base and the current exam model for access to higher education at the national level, National High School Examination, which, in a way, influences the high school teaching and learning process. In addition, in order to prepare the reader for a better understanding of our proposal, we will present a little of the Combinatorial Analysis studied in High School, chosen for being an easily contextualized and problematized content, besides the low performance index presented by the students in relation to it.